HARDNESS OF SPRING DURUM WHEAT KERNELS IN THE WEST SIBERIA - M. G. Evdokimov; V. S. Yusov; I. V. Pakhotina; M. N. Kiriyakova (Зерновое хозяйство России)
There have been presented study results of the spring durum wheat varieties grown in the southern forest-steppe area of the Omsk region on kernel hardness. The objects of research were the varieties of ecological variety testing conducted by various Russian and Ukrainian scientific institutions. The study was conducted in the period from 2003–2015. Experimental plots of 10 m2 were placed in 4 sequences. The varieties were sown in weedfree fallow. The soil of the experimental plot was weakly leached blackearth (chernozem), medium humus (6.2%), and loamy. The sowing date is 14–15 of May, the sowing rate is 4.5 million of germinated kernels per ha. The average hardness index in 2003–2015 was 70.1%. The varieties varied from 66.0 (the variety “Svetlana”) to 74.6% (the variety “Saratovskaya zolotistaya”). The differences between maximum and minimum were 8.6%. The variation through the years was from 51% to 92%, from 21% (the varieties “Angel”, “Omsky korund”) to 34% (the variety “Saratovskaya zolotistaya”). The calculated coefficient of variation showed that the variability degree ranged from little to medium. Coefficients of variation varied from 9.3% (the variety “Angel”) to 14.3% (the variety “Bezenchukskaya 182”). According to S. A. Eberhart, W. A. Russel the stability index indicates a lower variability of the varieties “Angel”, “Omsky korund”, “Altayskaya niva”, “Nik”, “Kharkovskaya 23”, “Tavolga”. The value of the regression coefficient (bi) for kernel hardness ranged from 0.77 to 1.23. The varieties “Voronezhskaya 9”, “Elizavetinskaya”, “Altayskaya niva”, “Omskaya stepnaya” and “Bezenchukskaya stepnaya” turned to be most responsive to the conditions (according to the Eberhart – Russell test). The varieties “Angel”, “Aleyskaya”, “Zarnitsa Altaya” had a weak reaction to the environmental conditions. There has been identified phenotypic correlation between the trait and productivity, 1000-kernel weight, nature weight, gluten quality, pasta color. The correlation between these traits is positive, on average r = 0.30–0.440.